Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the sum of the sequence [tex]$1 + 11 + 2 + 12 + 3 + 13 + \ldots + 19 + 29$[/tex], we need to carefully examine and break down the sequence into two distinct arithmetic sequences, then sum those sequences and add their results.
### Step 1: Identify the sequences
The given sequence can be split into two different arithmetic sequences as follows:
1. First arithmetic sequence (S1): 1, 2, 3, ..., 19
2. Second arithmetic sequence (S2): 11, 12, 13, ..., 29
### Step 2: Sum of the first arithmetic sequence (S1)
1. Identify the first term (a1) and the last term (l1):
- The first term for S1: [tex]\( a1 = 1 \)[/tex]
- The last term for S1: [tex]\( l1 = 19 \)[/tex]
2. Number of terms (n1) in the first sequence:
- Number of terms, n1: [tex]\( n1 = 19 \)[/tex]
3. Sum of the first sequence (S1) using the formula for the sum of an arithmetic sequence [tex]\( \text{Sum} = \frac{n}{2} \cdot (a + l) \)[/tex]:
[tex]\[ \text{Sum}_1 = \frac{19}{2} \times (1 + 19) = 19 \times 10 = 190 \][/tex]
### Step 3: Sum of the second arithmetic sequence (S2)
1. Identify the first term (a2) and the last term (l2):
- The first term for S2: [tex]\( a2 = 11 \)[/tex]
- The last term for S2: [tex]\( l2 = 29 \)[/tex]
2. Number of terms (n2) in the second sequence:
- Number of terms, n2: [tex]\( l2 - a2 + 1 = 29 - 11 + 1 = 19 \)[/tex]
3. Sum of the second sequence (S2) using the same formula:
[tex]\[ \text{Sum}_2 = \frac{19}{2} \times (11 + 29) = 19 \times 20 = 380 \][/tex]
### Step 4: Combine the results
To find the total sum of the given sequence, we add the sums of the two sequences:
[tex]\[ \text{Total Sum} = \text{Sum}_1 + \text{Sum}_2 = 190 + 380 = 570 \][/tex]
Therefore, the sum of the sequence [tex]\(1 + 11 + 2 + 12 + 3 + 13 + \ldots + 19 + 29\)[/tex] is [tex]\( 570 \)[/tex].
### Step 1: Identify the sequences
The given sequence can be split into two different arithmetic sequences as follows:
1. First arithmetic sequence (S1): 1, 2, 3, ..., 19
2. Second arithmetic sequence (S2): 11, 12, 13, ..., 29
### Step 2: Sum of the first arithmetic sequence (S1)
1. Identify the first term (a1) and the last term (l1):
- The first term for S1: [tex]\( a1 = 1 \)[/tex]
- The last term for S1: [tex]\( l1 = 19 \)[/tex]
2. Number of terms (n1) in the first sequence:
- Number of terms, n1: [tex]\( n1 = 19 \)[/tex]
3. Sum of the first sequence (S1) using the formula for the sum of an arithmetic sequence [tex]\( \text{Sum} = \frac{n}{2} \cdot (a + l) \)[/tex]:
[tex]\[ \text{Sum}_1 = \frac{19}{2} \times (1 + 19) = 19 \times 10 = 190 \][/tex]
### Step 3: Sum of the second arithmetic sequence (S2)
1. Identify the first term (a2) and the last term (l2):
- The first term for S2: [tex]\( a2 = 11 \)[/tex]
- The last term for S2: [tex]\( l2 = 29 \)[/tex]
2. Number of terms (n2) in the second sequence:
- Number of terms, n2: [tex]\( l2 - a2 + 1 = 29 - 11 + 1 = 19 \)[/tex]
3. Sum of the second sequence (S2) using the same formula:
[tex]\[ \text{Sum}_2 = \frac{19}{2} \times (11 + 29) = 19 \times 20 = 380 \][/tex]
### Step 4: Combine the results
To find the total sum of the given sequence, we add the sums of the two sequences:
[tex]\[ \text{Total Sum} = \text{Sum}_1 + \text{Sum}_2 = 190 + 380 = 570 \][/tex]
Therefore, the sum of the sequence [tex]\(1 + 11 + 2 + 12 + 3 + 13 + \ldots + 19 + 29\)[/tex] is [tex]\( 570 \)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.